(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Multimedia protection has become a significant problem in the society where the intellectual property is threatened. Digital watermarking can be considered as a solution to protect the multimedia. Property protection is a common field of research compared to other fields such as identity verification and local manipulation localization. Imperceptibility and robustness are the most crucial requirements for multimedia watermarking. High distortion is provided by watermarks with high robustness. We must so strike a balance between them. Recently many works based on frequency range which can satisfy watermarking requirements such as high robustness and low distortion. Visual attention based image watermarking is considered one of image watermarking methods due to detect the most important regions for watermark embedding. The lack of robustness against malicious cyber-attacks makes watermarks easily detectable and destroyed. As a result, the proposed watermarking scheme becomes more complex and cannot withstand diversity Geometric and non-geometric attacks. Therefore, there are many existing visual attentions based image watermarks. This paper analyzes the techniques for image watermarking against various types of attacks and presents the applications of digital watermarking.